Direct oral Xa inhibitors versus warfarin in patients with cancer and atrial fibrillation: a meta-analysis. Issue 8 (August 2020) - Casula, Matteo; Fortuni, Federico; Fabris, Francesca; Leonardi, Sergio; Gnecchi, Massimiliano; Sanzo, Antonio; Greco, Alessandra; Rordorf, Roberto
Abstract : Aims: Patients with cancer are at higher risk of atrial fibrillation, thromboembolic complications and bleeding events compared with the general population. The aim of the present meta-analysis was to compare the efficacy and safety of direct oral Xa inhibitor anticoagulants versus warfarin in patients with cancer and atrial fibrillation. Methods: We searched electronic databases for randomized controlled trials comparing direct oral Xa inhibitor anticoagulants and warfarin in cancer patients. The primary efficacy outcome was stroke or systemic embolism. The primary safety outcome was major bleeding. A subgroup analysis was performed to explore the outcome differences between patients with active cancer or history of cancer. Results: Three trials with a total of 3029 cancer patients were included in the analysis. There was no statistically significant difference in the risk of stroke or systemic embolism [risk ratio (RR) 0.76; 95% confidence interval (CI) 0.52–1.10] between the two therapeutic strategies. Direct oral Xa inhibitors significantly reduced the incidence of major bleeding compared with warfarin (RR 0.79; 95% CI 0.63–0.99; P = 0.04; number needed to treat = 113). These results were consistent both in patients with active cancer and in those with history of cancer. Conclusion: In patients with cancer and atrial fibrillation, direct oral Xa inhibitors have a similar efficacy and may be safer compared with warfarin. These results are consistent both in patients with active cancer and history of cancer. Abstract : Supplemental Digital Content is available in the text